Effects of weed density on the dispersal of Orius majusculus Reuter (Heteroptera Anthocoridae) within maize. (6th February 2015) - Madeira, F.; Pons, X.
Abstract Orius majusculus Reuter (Heteroptera: Anthocoridae) is the most common and abundant generalist predator in Spanish maize crops and is sensitive to drastic changes in weed density. We carried out a 2‐year study in the NE Iberian Peninsula to examine the dispersal of O. majusculus in maize plots with moderately high and low weed density. Insects were collected using yellow sticky traps and/or a bug‐vac aspirator. Dispersal was assessed using rubidium as a marker. Dispersal rate of O. majusculus differed between sampling periods, with a maximum between the 16 unfolded leaves (V16) to grain milky (R3) maize growth stages. However, we detected no differences in the distance moved by male and females of O. majusculus from rubidium‐marked areas in plots with moderately high or low weed density suggesting that changes in weed density do not affect the dispersal of O. majusculus within a maize field.